STRATEGI PENGEMBANGAN USAHATANI PADI SEMI ORGANIK PADA GAPOKTAN SALUYU DI DESA CILAMAYA KECAMATAN CILAMAYA WETAN KABUPATEN KARAWANG - Ismi Widiyawati; Wagiono Wagiono; Luthfi Nur’azkiya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Semi-organic farming is an alternative to organic farming, to create environmentally friendly agriculture which is free from chemicals. The purpose of the study is to analyze alternative strategies and strategic priorities in the development of semi-organic rice farming in Gapoktan Saluyu. The research method used a descriptive method with a mixed-method approach. The sample of farmers is 17 farmers and is determined by Probability Sampling, while the sample of stakeholders, namely extension workers, heads of Gapoktan Saluyu and the Agriculture Service of Karawang Regency, is determined by purposive method. The results showed that: (1) Producing five alternative strategies, namely increasing cooperation with various related marketing partnerships to reach and expand the market, improving postharvest handling, especially (milling and added value of packaging), increasing regular meetings of gapoktan specifically for semi-organic rice farming, the need for government and extension support in providing training on organic farming and filtration of irrigation water so that toxins carried by water can be  rivaled. (2) The priority strategy is to filtration irrigation water so that the poisons carried by the water can be filtered with a STAS value of 7,62.